Pollen morphology of Iranian Dracocephalum L. (Lamiaceae) and its taxonomic significance (Bangladesh Journal of Plant Taxonomy, 2015)
Pollen morphology of 11 Iranian Dracocephalum L. species was investigated using light and scanning electron microscopy to evaluate their taxonomic significance for the infrageneric classification of the genus. Pollen grains of all examined taxa were isopolar, hexacolpate, circular in polar view and spheroidal to prolate in equatorial view (P/E = 1.0?2.0). The smallest pollen grains were observed in D. aucheri (P = 29.7 ?m, E = 22.6 ?m), while the largest pollen was found in D. lindbergii (P = 45.1 ?m, E = 33.7 ?m). The highest and lowest apocolpium index (AI) were measured in D. aucheri (AI = 0.27) and D. surmandinum (AI = 0.08), respectively. Colpus membrane was egranulate in all examined species except for D. multicaule and D. ghahremanii. The main exine ornamentation type was characterized as bireticulate including five different subtypes. The results revealed that the exine ornamentation is a diagnostic character useful for the classification of Dracocephalum.Bangladesh J. Plant Taxon. 22(2): 99-110, 2015 (December)